Relatiewe sektor-verskuiwing: ’n vergelyking tussen drie berekenings-metodes - Claassen, PE (Town and Regional Planning, 1978)
In "Magazine for Regional Planning" No. 3, Prof. Page (1 p. 10) methods to determine the economic growth of a region. The "sectoral shift" or relative sector shift, as the author prefers to mention, has been proposed as a method of measuring economic progress in a region relative to the shift in the country as a whole, by employment in the industrial sectors at compare two consecutive sensing times. Table 1 gives an explanation of the method with the results of the operation in column 7, di. the profit or loss in employment in each sector measured by the national shift. The rational of relative sector shift is that a positive shift in sectors that have opportunities for rapid growth and negative shift in sectors that offer few growth prospects indicate that the region’s position has improved, and vice versa. *This article is written in Afrikaans.